Diferentes estratégias para as aulas de educação física e o impacto sobre a intensidade dos esforços, as percepções e o engajamento dos escolares - Gonçalves, Marcelo José Resende (2024)
Background & purpose: Previous studies have indicated that Physical Education classes do not provide sufficient time in moderate to vigorous intensity physical activity (MVPA) according to recommendations by international organizations. Thus, this study aimed to compare the intensity achieved using different strategies in Physical Education classes, and secondarily to investigate the fun, motivation, and engagement of students. Methods: In total, 52 students were included, 23 girls and 29 boys. A recreational strategy and an additional circuit/HIIT class were applied and compared with a traditional class. All classes were structured with the content of games and activities. The intensity was monitored using a portable heart rate monitor and the subjective perception of exertion (RPE) was recorded. For comparisons between each class strategy, the Kruskal-Wallis test and Dunn's test were applied to locate significant differences (P<0.05), as well as for comparisons of heart rate (HR) and RPE. Qualitative data are presented as percentages of interview responses. Results: The circuit/HIIT and recreational strategy showed significant superiority (P<0.01) in the proportions of time in MVPA compared to the traditional class. The RPE supported the quantitative results of HR in class intensities. The qualitative results showed that the recreational class gained the highest number of positive responses, followed by the traditional class, while the circuit/HIIT received fewer positive responses. Conclusion: The circuit/HIIT was the strategy that achieved the highest percentages in MVPA, followed by the recreational and traditional classes. All classes achieved values greater than 50% of class time in MVPA. Qualitatively, the results showed greater fun, motivation, and engagement among students in the recreational model, followed by the traditional class, and, finally, the circuit/HIIT.